Meios de vida das famílias rurais: um estudo da influência das políticas públicas de inclusão produtiva na divisão sexual do trabalho rural - Petarly, Renata Rauta (2023)
This thesis analysed whether access to public policies for productive inclusion for family farming influenced the livelihoods and the sexual division of labour within those families that accessed them. With the research methods used, we sought to understand how the social space of family farming is organized and how the habitus was restructured from the moment these families accessed the PAA and PNAE policies. The municipality of Wanderlândia, in the state of Tocantins, was chosen for being the one that most accessed the PAA in the state on a perennial basis in its years of execution. This was the fundamental criterion for choosing the municipality, as it would make it possible to understand whether the insertion of families into unoccupied spaces and practices that had not been carried out before and the requirements of the public policy bureaucracy had changed the livelihoods of family productive units. To achieve the research objective, 41 questionnaires were applied to all family farmers who accessed the programs, reaching 100% of their population. The questionnaire data were analysed using Multiple Correspondence Analysis (MCA) and by its contribution method, resulting in a total of 108 active categories and 3 axes of contribution to the inertia of the constituted social space. Another method of data collection used was in-depth interviews with 15 families, prioritizing data collection with women. These women were identified from the construction of the social space in the MCA, prioritizing greater diversity in different regions of the social space. Observation and annotation in a field notebook was also a method used to identify information that was unspoken but perceived during fieldwork. The postures, positions and who were the members who answered each question were observed. To account for the objective of this thesis, the Bourdieusian theory of social space, habitus and symbolic power were used as theoretical lenses; complemented by gender studies and feminist economics, rural studies and the sociology of money. With the collected data, it is possible to conclude that the families that accessed these public policies occupy different positions in the social space of the family farming in Wanderlândia and that the access to the PAA and the PNAE caused several changes within the families: these were changes in the sexual division of work, in the gender tags of certain products and larger presence of women in public spaces by the end of the access to the programs – roles that were not previously occupied by them. Thus, it is possible to affirm as true the hypothesis that access to public policies for productive inclusion caused changes in the livelihoods of the families that access it and, consequently, the reconversion of these families' habitus.